Effect of wrist and forearm training on linear bat-end, center of percussion, and hand velocities and on time to ball contact of high school baseball players - Szymanski, D. J.; McIntyre, J. S.; Szymanski, J. M.; Molloy, J. M.; Madsen, N. H.; Pascoe, D. D. (The Journal of Strength and Conditioning Research, 2006)
This study examined the effects of 12 weeks of wrist and forearm training on linear bat-end velocity (BV), center of percussion velocity (CV), hand velocity (HV), and time to ball contact of high school baseball players. Forty-three baseball players were randomly assigned by a stratified sampling technique to 1 of 2 training groups. Group 1 (n = 23) and group 2 (n = 20) performed the same full-body resistance exercises while training 3 days a week for 12 weeks according to a stepwise periodized model. Group 2 also performed wrist and forearm exercises 3 days a week for 12 weeks. Wrist and forearm strength were measured pre- and posttraining. Linear BV, CV, HV, and time to ball contact were recorded pre- and posttraining by a motion-capture system. A 3 repetition maximum (RM) parallel squat and bench press were measured at baseline and after 4, 8, and 12 weeks of training. Both groups showed statistically significant increases (p 0.01) in linear BV, CV, and HV (m·s-1 ± SD) after 12 weeks of training; however, there were no differences between the 2 groups. Both groups statistically increased wrist and forearm strength (p 0.05). Group 2 had statistically greater increases (p 0.05) in 10 of 12 wrist and forearm strength measures than did group 1. Both groups made statistically significant increases in predicted 1RM parallel squat and bench press after 4, 8, and 12 weeks of training; however, there were no differences between groups. These data indicate that a 12-week stepwise periodized training program can significantly increase wrist and forearm strength, linear BV, CV, and HV among high school baseball players. However, increased wrist and forearm strength did not contribute to further increases in linear BV, CV, or HV.